2012
DOI: 10.1371/journal.pone.0041115
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Eimeria tenella Apical Membrane Antigen-1 (AMA1)

Abstract: Apical membrane antigen-1 (AMA1) is a micronemal protein of apicomplexan parasites that appears to be essential during the invasion of host cells. In this study, a full-length cDNA of AMA1 was identified from Eimeria tenella (Et) using expressed sequence tag and the rapid amplification of cDNA ends technique. EtAMA1 had an open reading frame of 1608 bp encoding a protein of 535 amino acids. Quantitative real-time PCR analysis revealed that EtAMA1 was expressed at higher levels in sporozoites than in the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 40 publications
6
75
0
Order By: Relevance
“…In contrast, application of Fu and Li's D* and F* tests indicated low levels of balancing selection. Combined, these findings suggest a low level of balancing selection within specific, possibly epitope-coding, regions that is consistent with the incomplete nature of the immune protection attributable to AMA1 revealed when tested as a recombinant protein or DNA vaccine (14,26). The relatively short and apparently self-limiting in vivo Eimeria lifecycle also is likely to reduce the magnitude of antigen-specific immune selection.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In contrast, application of Fu and Li's D* and F* tests indicated low levels of balancing selection. Combined, these findings suggest a low level of balancing selection within specific, possibly epitope-coding, regions that is consistent with the incomplete nature of the immune protection attributable to AMA1 revealed when tested as a recombinant protein or DNA vaccine (14,26). The relatively short and apparently self-limiting in vivo Eimeria lifecycle also is likely to reduce the magnitude of antigen-specific immune selection.…”
Section: Discussionsupporting
confidence: 59%
“…As recombinant or vectored subunit anticoccidial vaccines become technically more feasible, the regional occurrence of each Eimeria species and the extent of vaccine-targeted antigenic diversity assume greater relevance (5,14). Under experimental conditions, studies with clonal reference strains of Eimeria have found antigens such as AMA1 to induce good levels of immunoprotection (14,26). AMA1 also is an effective vaccine candidate in related apicomplexans including Neospora caninum, T. gondii, and several Plasmodium species (27)(28)(29)(30), but its value for Plasmodium has been undermined by high levels of naturally occurring antigenic diversity (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated the importance of EteIF3s7 in host cell invasion in invasion inhibition experiments. In our previous study, we showed that some anti-protein specific polyclonal antibodies reduced E. tenella sporozoites invasion in vitro (Han et al, 2013;Jiang et al, 2012b). In our current study, the reduced capacity of sporozoites preincubated with an anti-rEteIF3s7 polyclonal antibody to invade DF-1 cells demonstrated the importance of EteIF3s7 in host cell invasion.…”
Section: Discussionsupporting
confidence: 60%
“…The PCR primers for EtSIR2A were as follows: 5′-AAA AGA AAC TTC CTC CCA-3′and 5′-AAT CCT GTC TCC TCC AAA-3′. Three housekeeping genes of E. tenella , 18S rDNA, β-actin and gapdh , were used as reference genes for the purposes of normalization [2628]. The qPCR reaction mixture (20 μl) contained 10 μl SYBR® Premix Ex Taq™ (2×) (TaKaRa), 1 μl (0.2 μM) of each primer, 1 μl of cDNA template and 7 μl RNase-free distilled H 2 O.…”
Section: Methodsmentioning
confidence: 99%